TINGKAT PEMAHAMAN MASYARAKAT NAGARI TANDIKAT KECAMATAN PATAMUAN KABUPATEN PADANG PARIAMAN TENTANG MITIGASI BENCANA GEMPA BUMI - 184-189 . Septia Rahman (Universitas Negeri Padang, 2013)
This research is a descriptive study aimed to reveal the extent of public awareness about disaster mitigation Nagari Tandikat earthquake. Understanding the observed include: 1) Knowledge of earthquake disaster mitigation, 2) Knowledge about earthquakes, 3) Knowledge of the construction of earthquake-friendly buildings, 4) Understanding of mitigation policies, 5) An understanding of earthquake preparedness, 6) An understanding of the structure of friendly buildings quake. The populationin this studyispeople inas many as11,060people Tandikat Nagariandsamples usedby 95people, samplingtechniquestratified randomsampling. Types of data usedare primary dataobtained fromquestion nairesdistributedto the community. Samples wereclassifiedaccording tosocialstatus. The dataanalysis techniqueswithdescriptive statistical analysisusingthe percentage formulathendescribedin narrative form. The analysis showedthat the level ofpublic awarenessaboutthe earthquakedisaster mitigation, themitigationknowledge, general knowledge ofearthquakes andearthquakefriendlybuilding constructionknowledgeis still relativelymoderatesoialnyastatusin each group, exceptfor thesub-indicatorsof knowledgemitigation. Understanding ofmitigationismitigation policies, earthquakepreparednessandimplementation ofearthquake-friendly structureis still a relativelylowsocialstatusgroupsat eachcommunity. Key words : mitigation, earthquake, public understanding.